PERANCANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA CV JUNG JAYA PALEMBANG MENGGUNAKAN MICROSOFT ACCESS - Dwitayanti, Yevi; Putri, Silva Khairani; Oktarida, Anggraeni (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2025)
This Acivity aims to design and develop a computerized cash sales accounting information system using Microsoft Access at CV Jung Jaya Palembang to make it easier to manage sales transactions. Its main features include automatic recording of cash receipts journals, general ledgers, and generation of sales reports. The method used was secondary data collection and direct interviews at CV Jung Jaya Palembang. This system is designed using tables, queries, forms, and reports. The development process includes system design into tables, queries and forms that produce output in the form of Sales Reports. With a sales accounting information system, companies can optimize financial management, especially in cash receipts from cash sales transactions.